Unlocking the enigma of social commerce discontinuation: exploring the approach and avoidance drivers - Chong, Sin-Er; Lim, Xin-Jean; Ng, Siew Imm; Kamal Basha, Norazlyn (Emerald Publishing, 2025)
Purpose: This research explores the impact of approach and avoidance drivers on users’ discontinuance usage intention (DUI) in social commerce (s-commerce). It also examines the mediating role of perceived enjoyment and the moderating role of autotelic personality traits. Design/methodology/approach: Using a purposive sample of 465 s-commerce users in Malaysia, data analysis was conducted using partial least squares structural equation modeling (PLS-SEM). Findings: This study demonstrates that informational support is a key approach driver, enhancing perceived enjoyment and reducing perceived deception and DUI. Although perceived deception does not directly affect perceived enjoyment, it significantly predicts DUI. Additionally, the impact of informational support on DUI is mediated by perceived enjoyment and moderated by autotelic personality. Practical implications: S-commerce stakeholders, including platform developers, sellers and policymakers, can leverage these findings to foster a sustainable s-commerce environment. Implementing the proposed strategies can enhance perceived enjoyment and reduce DUI among current users. Originality/value: This research advances s-commerce marketing and IS discontinuance studies by extending the approach-avoidance motivations model (AAMM) into s-commerce and incorporating autotelic personality as a moderating factor provides new insights into user DUI in this evolving field.